Time-resolved THz Stark spectroscopy of molecules in solution - Kang, Bong Joo; Rohwer, Egmont J.; Rohrbach, David; Zyaee, Elnaz; Akbarimoosavi, Maryam; Ollmann, Zoltan; Sorohhov, Gleb; Borgoo, Alex; Cascella, Michele; Cannizzo, Andrea; Decurtins, Silvio; Stanley, Robert J.; et al. (Nature communications, 2024)
For decades, it was considered all but impossible to perform Stark spectroscopy on molecules in a liquid solution, because their concomitant orientation to the applied electric field results in overwhelming background signals. A way out was to immobilize the solute molecules by freezing the solvent. While mitigating solute orientation, freezing removes the possibility to study molecules in liquid environments at ambient conditions. Here we demonstrate time-resolved THz Stark spectroscopy, utilizing intense single-cycle terahertz pulses as electric field source. At THz frequencies, solute molecules have no time to orient their dipole moments. Hence, dynamic Stark spectroscopy on the time scales of molecular vibrations or rotations in both non-polar and polar solvents at arbitrary temperatures is now possible. We verify THz Stark spectroscopy for two judiciously selected molecular systems and compare the results to conventional Stark spectroscopy and first principle calculations. Stark spectroscopy of molecules in liquid solutions was once challenging due to orientation effects, solved by freezing but limiting ambient studies. Now, THz Stark spectroscopy with intense terahertz pulses enables dynamic analysis of molecules in both non-polar and polar solvents at any temperature, advancing conventional methods.